Investigation of cross talk in single grain luminescence measurements using an EMCCD camera - Gribenski, Natacha; Preusser, Frank; Greilich, Steffen; Huot, Sebastien; Mittelstraß, Dirk (Radiation measurements, 2015)
Highly sensitive electron multiplying charges coupled devices (EMCCD) enable the spatial detection of luminescence emissions from samples and have a high potential in single grain luminescence dating. However, the main challenge of this approach is the potential effect of cross talk, i.e. the influence of signal emitted by neighbouring grains, which will bias the information recorded from individual grains. Here, we present the first investigations into this phenomenon when performing single grain luminescence measurements of quartz grains spread over the flat surface of a sample carrier. Dose recovery tests using mixed populations show an important effect of cross talk, even when some distance is kept between grains. This issue is further investigated by focusing just on two grains and complemented by simulated experiments. Creation of an additional rejection criteria based on the brightness properties of the grains is inefficient in selecting grains unaffected by their surroundings. Therefore, the use of physical approaches or image processing algorithms to directly counteract cross talk is essential to allow routine single grain luminescence dating using EMCCD cameras.
Online verfügbar: 28. Januar 2015, Artikelversion: 21. Oktober 2015
Gesehen am 04.02.2026